2017
DOI: 10.1103/physrevphyseducres.13.020126
|View full text |Cite
|
Sign up to set email alerts
|

Peer assessment of student-produced mechanics lab report videos

Abstract: We examine changes in students' rating behavior during a semester-long sequence of peer evaluation laboratory exercises in an introductory mechanics course. We perform a quantitative analysis of the ratings given by students to peers' physics lab reports, and conduct interviews with students. We find that peers persistently assign higher ratings to lab reports than do experts, that peers begin the semester by giving high ratings most frequently and end the semester with frequent middle ratings, and that peers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…SGV can be applied in a wide range of subjects related empirical study, commonly found in the discipline of pure science, such as physics (Douglas et al, 2017), chemistry (e.g. Jordan et al, 2016), and biology (Pirhonen & Rasi, 2017).…”
Section: Discipline-specific Application Of Sgvmentioning
confidence: 99%
“…SGV can be applied in a wide range of subjects related empirical study, commonly found in the discipline of pure science, such as physics (Douglas et al, 2017), chemistry (e.g. Jordan et al, 2016), and biology (Pirhonen & Rasi, 2017).…”
Section: Discipline-specific Application Of Sgvmentioning
confidence: 99%
“…Our data was collected in a calculus-based introductory mechanics course in the Fall 2013 semester taught using a flipped model at the Georgia Institute of Technology. At the time of the data collection, the course used the Matter & Interactions curriculum [7] while implementing short video lectures [1,2] in addition to in-class problem solving and novel laboratory activities [8,9]. Students' enrolled in the course spent class time focused on various problem solving activities.…”
Section: Datamentioning
confidence: 99%
“…The presentations were then peer-evaluated and graded [8]. These grades have been shown to serve as a reasonable proxy for expert grades [8][9][10]. Students were allowed to drop one of the laboratory grades and therefore, some students did not participate in all exercises; these entries were graded as zero and were removed from the analysis.…”
Section: Datamentioning
confidence: 99%